COMPARATIVE STUDY OF FUNCTIONAL OUTCOME COMPARING POSTERIOR CRUCIATE LIGAMENT SUBSTITUTING PRIMARY KNEE ARTHROPLASTY WITH PRIMARY KNEE ARTHROPLASTY USING ULTRACONGRUENT TIBIAL ARTICULAR INSERT AFTER COMPLETE RELEASE OF POSTERIOR CRUCIATE LIGAMENT - GAJBHIYE, DEWENDRA J; MITTAL, GAURAV; ROUT, ASHOK; SINGH, SANTOSH KUMAR; KEDAR, PRADEEP (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to compare the functional outcome of posterior cruciate ligament (PCL) substituting primary knee arthroplasty with primary knee arthroplasty using ultra-congruent (UC) tibial articular insert after complete release of PCL. The study aimed to compare the stability of the knee joint after PCL sacrifice for degenerative arthritis of the knee. Methods: This was a prospective, randomized, double blind, and single-center study. After approval by the Institutional Ethical Committee, 80 patients, 40 in each group (UC and posterior stabilized [PS]) of either sex, aged between 60 and 80 years and willing to participate in the study were included in the study. Patients underwent primary knee arthroplasty with either UC or PS implants using simple random sampling method. Each patient was followed up at 6 months, 1 year and between 5 and 7 years postoperatively and the functional results were assessed using Modified Knee Society Score (Insall modification -1993). Results: Around 73% of the patients were women and the average age was 67 years in line with the known literature confirming increased incidence of osteoarthritis requiring total knee arthroplasty in women and older individuals. There was a significant relief in pain and improvement in stair climbing ability after surgery. There was a reduction in flexion contractures, medial/lateral instability, and anterior posterior instability postoperatively. The improvement in range of motion was significantly in the UC group as compared to PS group. Similarly, the total score was significantly higher in the UC group as compared to PS. Conclusion: If functional outcomes are taken into consideration, UC prosthesis is better than the PS prosthesis. Further randomized and double-blinded clinical trials with larger sample size and longer duration follow-up need to be conducted to validate the findings.